How Guest Perceived Green Hotel Practice. A Study of Indonesia - LEMY, Diena Mutiara; BRIAN, Reagan; PAH, Jacob Ganef (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.v10.8(40).07, 2020)
Increasing awareness toward environmental conservation brings up the green hotel practice being applied into hotel daily operation. All the green practice done by the hotel supposedly beneficial for the environment without harming the service quality given to the guest. In fact, result from some studies has shown that not all guests have good perception towards green hotel practices. In regards with Indonesia, there are limited studies exploring the relationship between hotel guests and green hotel practice. This study tries to find out about how the guest perceived the green hotel practices. This study also exploring which green hotel attributes that most appealing to the guests. The survey was conducted in two major cities in Indonesia: Jakarta and Bandung. This study collect data with convenience sampling method and use descriptive analysis to explain it. The findings show that guest have positive attitude toward green hotel practice as long as their convenience and comfort during stay are not disturbed, and the price of the service are not increase because of green hotel practice. Based on the findings, it can be said that guest’s attitude is positive toward green hotel practice in Indonesia.